Does curriculum reform influence perceived preparedness for practice of graduates? A comparison of two cohorts. (1st August 2019) - Parmar, Harsha; Schafheutle, Ellen; Willis, Sarah; Silkstone, Victoria
Abstract: Objectives: Using performance standards (PS) set by the General Pharmaceutical Council (GPhC), this study compared the views of two consecutive cohorts of MPharm graduates from one pharmacy school, pre- and postcurriculum reform on preparedness for practice (PFP). Methods: Preparedness was investigated using the GPhC's 76 PS, grouped into three domains of practice: professional activity, interpersonal skills and ability to provide an effective pharmaceutical service. Respondents were asked to (dis)agree with how they perceived the MPharm had sufficiently prepared them to meet each of the 76 PS. Differences in mean score between the two cohorts were analysed via the independent-samples t-test. Regression analysis was used to determine whether the year of graduation was a predictor of PFP once other variables were controlled for. Key findings: A response rate of 30.1 and 42.4% was achieved for the 2014 and 2015 cohort, respectively. Significantly more respondents of the 2015 cohort (postcurricular reform) felt prepared for practice than respondents of the 2014 cohort (precurricular reform), for all domains of preregistration performance standards. Multiple regression analysis demonstrated that year of graduation was the independent variable that made the strongest unique contribution to explaining PFP (β = 0.527, P ≤ 0.005). Conclusions: Overall findings of this study suggest that increasing adoption of undergraduate active learning opportunities and integrating learning of core subjects may enhance the overall feeling of preparedness for practice.